Removal Efficiency of Total Chrome (Cr-T) from Textile Industry Wastewater PT. X with Sodium Bentonite Using the Adsorption Method - Etih Hartati; Raisa Nur Azizah; Dyah Marganingrum (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
As much as 10-50% of dye wastewater from the dyeing process is discharged directly into the environment. Chromium is the metal most often found in textile industry wastewater, one of which comes from dyes of the Congo Red type, so processing is required. One of the treatments to remove total chromium from textile industry wastewater is adsorption, with sodium bentonite as an adsorbent. This study aimed to determine the optimum efficiency and processing of total chromium using sodium bentonite as an adsorbent with a batch system and to determine the appropriate type of isotherm. The method used to test total chromium was the standard addition method which was then measured using an AAS (Atomic Absorption Spectrophotometry). The variables studied were the effect of wastewater pH, sodium bentonite and grain size of wastewater on the efficiency of total chromium removal. The types of isotherms tested are Langmuir and Freundlich isotherms. In removing total chromium with sodium bentonite, optimum conditions were obtained at pH 8 with a grain size of 80 mesh and a volume of 50% wastewater with a removal efficiency of 98.08%. The appropriate isotherm model for sodium bentonite is the Freundlich isotherm.